1998
DOI: 10.1046/j.1526-4610.1998.3810782.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Associated With Pituitary Adenomas

Abstract: The objectives of this study were to analyze the characteristics of headache in patients with pituitary adenoma and to investigate the mechanisms involved. Fifty-one patients (27 females and 24 males) with pituitary adenoma were examined. Nineteen (37.3%) of these patients (13 females and 6 males) had headache preoperatively. Most commonly, the headache was generalized (42.1%); overall headache was more frequent in the anterior half of the head (84.2%). Seventeen (89.5%) patients had bilateral headache. Headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
120
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 0 publications
10
120
1
1
Order By: Relevance
“…The widespread availability of advanced neuroradiological instruments has increased the chances of detecting patients with both pituitary adenoma and headaches. Headache is one of the major symptoms of pituitary adenoma, with a prevalence of 33-72%, although neurosurgeons occasionally cannot decide whether the pituitary adenoma causes the headache [4,5]. If the conventional medical treatment (multiple regimens, such as non-steroidal anti-inflammatory drugs, triptans, and antidepressant) proves ineffective, it would be necessary to make final decisions on whether to operate for the pituitary adenoma [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread availability of advanced neuroradiological instruments has increased the chances of detecting patients with both pituitary adenoma and headaches. Headache is one of the major symptoms of pituitary adenoma, with a prevalence of 33-72%, although neurosurgeons occasionally cannot decide whether the pituitary adenoma causes the headache [4,5]. If the conventional medical treatment (multiple regimens, such as non-steroidal anti-inflammatory drugs, triptans, and antidepressant) proves ineffective, it would be necessary to make final decisions on whether to operate for the pituitary adenoma [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the incidence of headache was 57.1% in non-functioning adenomas [7] and 60% in GH-secreting adenomas [8]. Headache seems to be more frequent in prolactin (PRL)-secreting adenomas (57.1%) than in GHsecreting adenomas (12.5%) [9]. Headache, more frequently localised to the frontal region, is bilateral (89.5%) or monolateral (84.2%) and sometimes diffuse (42.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Pain is continuous or pressing-heavy, and rarely pulsating-intermittent (mostly in female patients) (57.9%) [9]. Headaches due to GH-secreting adenomas, with or without acromegaly, do not have significant sellar abnormalities or visual problems [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there was no clear relationship between the pituitary volume and headache score. 8,9 Many patients report headaches after starting pharmacotherapy for adenoma; one explanation given for why headaches get worse after taking dopamine agonist is that the growth of the tumor is transitory or that a neurohormonal mechanism is possible. 10,11 The degree of extension into the cavernous sinus is not associated with the presence or extent of headache.…”
Section: Discussionmentioning
confidence: 99%